Effect Analysis of Post Heating Temperature Variation on Metallography and Bending Test of GMAW ASTM A53 Steel Weld Joint - Pratikno, Herman; Jafa, Muhammad Rizqy; Ikhwani, Hasan (Pusat Publikasi Ilmiah Institut Teknologi Sepuluh Nopember, 2022)
ASTM A53 steel is medium carbon steel with 0.3% carbon content and is often used for pipe manufacturing. The purpose of this study was to determine the effect of post heating temperature variation on bending and metallography test on weld joint of ASTM A53 steel using the GMAW process. The electrode used is ER-70S-6. Post heating temperature variations are 250oC, 300oC and 350oC. The bending test result showed that welding with 350oC postheating temperature produce the smallest open defect value. The microstructure result showed that welding with 350oC post heating temperature produce the smallest pearlite percentage in three areas observed.